2015
DOI: 10.1097/ijg.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Acute Angle-Closure Glaucoma in a Patient With Miller Fisher Syndrome Without Pupillary Dysfunction

Abstract: This is the first reported case of a patient with MFS without autonomic dysfunction and AACG. We believe that pupillary dysfunction or lid ptosis due to neurological disorders may increase the possibility of AACG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…[ 2 ] MFS patients with acute angle closure glaucoma have been reported, and most of them were related to ocular autonomic nerve involvement. [ 3 5 ] In this report, it was extremely rare that ophthalmoplegia, ataxia, and loss of tendon reflex did not appear in the early stage of MFS, but mydriasis and elevated intraocular pressure were the main manifestations. The first diagnosis was difficult, and the order of involvement of the oculomotor nerve, trochlear nerve, abducens nerve, and ciliary ganglion enriched with GQ1b ganglioside were considered.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[ 2 ] MFS patients with acute angle closure glaucoma have been reported, and most of them were related to ocular autonomic nerve involvement. [ 3 5 ] In this report, it was extremely rare that ophthalmoplegia, ataxia, and loss of tendon reflex did not appear in the early stage of MFS, but mydriasis and elevated intraocular pressure were the main manifestations. The first diagnosis was difficult, and the order of involvement of the oculomotor nerve, trochlear nerve, abducens nerve, and ciliary ganglion enriched with GQ1b ganglioside were considered.…”
Section: Discussionmentioning
confidence: 74%
“…[ 1 ] Pupil abnormality caused by autonomic nerve involvement account for about 33.7% of MFS. [ 2 ] It has been reported that acute angle closure glaucoma could occur due to autonomic nerve involvement in the course of MFS, [ 3 5 ] but there were no reports of acute angle-closure glaucoma as the first manifestation of the MFS. In this paper, we present a case of MFS with acute angle-closure glaucoma as the first manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…a slov. Oftal., 75, 2019, No.4 [18,120,51]. Naše 71letá pacientka byla rovněž v pásmu hypermetropie, axiální délka oka pravého oka byla 22,38 mm, levého oka 22,26 mm.…”
Section: Kazuistikaunclassified
“…Many clinical and immunologic studies have investigated MFS since the discovery of the anti-GQ1b-ganglioside antibody 145678910. However, few studies—and especially ones conducted by neuro-ophthalmologists—have systematically explored ocular motility, even though ophthalmoplegia is the most-common, disabling, and consistent finding in MFS.…”
Section: Introductionmentioning
confidence: 99%